Peran Perempuan Perspektif K.H Misbah Mustofa dalam Tafsir Al-Iklil Fi Ma'ani At-Tanzil - Nur Aliza Mabruroh (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
This research is motivated by the existence of an interpretive thought in the Javanese tradition which places women in a position that is more mobile in the domestic area. Because of the public perception that men see men's positions as having more potential than women, women are given less space in the public sector because men have a greater responsibility towards women. In one of the interpretive works from the Javanese tradition, namely al-Iklil fi Ma'ani al-Tanzil by Misbah Mustafa, an understanding is found that the role of men is more important than women. With this, the author uses a descriptive-analytical method by taking data from the research library. The results of the research show that Misbah Mustafa's thoughts in his interpretation of al-Iklil regarding the role of women are moderate, where Misbah Mustafa does not completely limit the role of women like traditionalists and not feminists who do not give women wide freedom because the nature of a woman is to be guarded and guided. by men. This article reflects on how social and cultural construction influences Misbah Mustafa's interpretive patterns in his work Tafsir al-Iklil